PRMT5-mediated methylation of METTL3 promotes cisplatin resistance in ovarian cancer by facilitating DNA repair mechanisms - Qiaoxi Xia; Ronghui Zhong; Jingfang Zheng; Xiao Zhou; Xinwei Zhao; Sisi Wang; Botao Wang; Quanfeng Wu; Chen Xie; Beihua Kong; Qing Zhang; Tianzhi Huang (Cell Reports)
Summary: Cisplatin (CDDP) is a widely used chemotherapy drug for treating various solid tumors. However, resistance to CDDP significantly hampers patient outcomes. This study reveals that protein arginine methyltransferase (PRMT)5 methylates METTL3 at the R36 residue (METTL3-R36me2), which is crucial for CDDP resistance in ovarian cancer (OC) cells. Following CDDP exposure, MST4 is transactivated by nuclear factor-erythroid 2-related factor 2 (NRF2), a key regulator of antioxidant responses. MST4 stimulates PRMT5’s methyltransferase activity and promotes its interaction with METTL3 via phosphorylation at Ser439 and Ser463, resulting in increased levels of METTL3-R36me2 and mRNA methylation at the N6 position of adenosine (m6A). The METTL3-R36me2 is recruited to DNA damage sites to promote RAD51 recruitment for homologous recombination (HR)-mediated double-strand break repair (DSBR) and enhance CDDP resistance. Importantly, targeting METTL3-R36me2 through inhibition of PRMT5 or METTL3 disrupts HR-DSBR and augments the cytotoxic effects of CDDP in ovarian tumor xenografts. Therefore, we conclude that METTL3-R36me2 represents a viable therapeutic target for overcoming CDDP resistance in OC.